ANALISIS KEBIJAKAN KEUANGAN PEMERINTAH INDONESIA DI MASA PANDEMI HINGGA PEMULIHAN EKONOMI NASIONAL PERIODE 2020-2024 - Mohamad Syakir (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2025)
The basic principle of law and policy is that social problems require policy as a concrete manifestation of government intervention to resolve them, whether through government action or inaction. However, to intervene, the government requires law and policy as instruments to protect the outcomes of jointly agreed policy agreements, which also reflect the protection of human interests from various social problems. Therefore, the state has a vital role in providing comprehensive, universal, and non-discriminatory welfare to its citizens, as mandated by the Preamble to the 1945 Constitution of the Republic of Indonesia, which is to improve the welfare of the people under the authority and power of the President of the Republic of Indonesia. The type of research applied in this study is descriptive normative research. This method, the truth of the information is explored through a review of documents, articles on financial policies during the pandemic from verified journals, and official records taken from official government websites regarding financial policies during the pandemic and National Economic Recovery for the 2020-2024 period. The results of this discussion indicate that various government policies related to state revenue and spending have been allocated appropriately for accessibility and connectivity in various aspects, including infrastructure, education, health, social, and political aspects. From the perspective of Maqasid al Shari'ah, all policies must be based on the principles of dharuriyat, hajiyaat, and tahsiniyaat. Dharuriyaat exerts protective power through teachings and fundamental principles in living life. Hajiyaat serves as a source of development for human thought, experimentation, and never-ending exploration. Meanwhile, tahsiniyaat is a human expression of God's omnipotence, generosity, and limitlessness in appointing humans as caliphs on earth. Based on these three principles, the Indonesian government's financial policy has implemented safeguards for religion, life, intellect, descendants, property, and other aspects, including environmental preservation, socio-political policies, and human rights.